Enhanced attentional bias towards sexually explicit cues in individuals with and without compulsive sexual behaviours. - Daisy J Mechelmans; Michael Irvine; Paula Banca; Laura Porter; Simon Mitchell; Tom B Mole; Tatyana R Lapa; Neil A Harrison; Marc N Potenza; Valerie Voon (PLoS ONE)
Compulsive sexual behaviour (CSB) is relatively common and has been associated with significant distress and psychosocial impairments. CSB has been conceptualized as either an impulse control disorder or a non-substance 'behavioural' addiction. Substance use disorders are commonly associated with attentional biases to drug cues which are believed to reflect processes of incentive salience. Here we assess male CSB subjects compared to age-matched male healthy controls using a dot probe task to assess attentional bias to sexually explicit cues. We show that compared to healthy volunteers, CSB subjects have enhanced attentional bias to explicit cues but not neutral cues particularly for early stimuli latency. Our findings suggest enhanced attentional bias to explicit cues possibly related to an early orienting attentional response. This finding dovetails with our recent observation that sexually explicit videos were associated with greater activity in a neural network similar to that observed in drug-cue-reactivity studies. Greater desire or wanting rather than liking was further associated with activity in this neural network. These studies together provide support for an incentive motivation theory of addiction underlying the aberrant response towards sexual cues in CSB.